Pengaruh Efektivitas Sistem Informasi Akuntansi, Kesesuaian Tugas, Kenyamanan Fisik dan Lingkungan Kerja pada Kinerja Karyawan - Sridarmaningrum, L. G.; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi; Vol 23 No 3 (2018), 2018)
Employee performance affects the success of a company, including financial institutions both bank and non-bank financial institutions such as Lembaga Perkreditan Desa (LPD). The purpose of this study is to determine the effect of effectiveness of the application of accounting information system (SIA), suitability of tasks, physical comfort and work environment on the performance of LPD employees in Denpasar City. The population in this study are employees who use computerized system of 212 people in LPD in Denpasar City. Sampling method used is nonprobability sampling method. Total samples taken as many as 105 people associated with SIA. The data was collected by distributing questionnaires, interviews and observations to LPDs in Denpasar City. The analysis technique used multiple linear regression analysis. The results of this study indicate that the effectiveness of the implementation of SIA, suitability, physical comfort and work environment have a positive effect on employee performance.